Midwives' Knowledge and Preparedness in Providing Maternity Care During COVID-19 Pandemic in Dodoma Region, Tanzania: A Cross-Sectional Study - Subira Abdalla; Angelina A. Joho (SAGE Publishing, 2022)
Background COVID-19 pandemic has a high impact on the health of pregnant women and healthcare providers worldwide. Objective This study aims to assess midwives' knowledge and preparedness in providing maternity care during COVID-19 pandemic. Methods A cross-sectional analytical hospital-based study that included 116 midwives, who were working in labor ward, was conducted in the Dodoma region of Tanzania from March to June 2021. The Chi-square test and Fisher's exact test were used to assess the association between the categorical variables. The predictors of midwives' knowledge and preparedness were determined using binary logistic regression analysis. Statistical analysis was performed using SPSS version 23.0; p  < .05 was considered to be significant. Results Of the midwives studied, 63 (54.3%) had adequate knowledge about COVID-19 and only 30 (25.9%) were adequately prepared on provision of maternal care. Having diploma/bachelor level of education (AOR  =  2.62, 95%CI  =  1.08-6.36, p   =  .033), being trained on COVID-19 (AOR  =  3.65, 95%CI  =  1.11-12.00, p   =  .033) and working in urban health facilities (AOR = 3.65, 95%CI  =  1.17-13.98, p   =  .002) were the significant determinants of midwives' knowledge on COVID-19. Working at a health center (AOR  =  0.19, 95%CI  =  0.03-1.32. p   =  .033), being trained on COVID-19 (AOR  =  0.04, 95%CI  =  0.01-0.14, p   =  .000 and having adequate knowledge on COVID-19 (AOR  =  0.20, 95%CI  =  0.03-1.32, p   =  .032) were determinants of midwives' preparedness on provision of maternal care. Conclusion Knowledge and preparedness in the provision of maternity care during the COVID-19 pandemic were low. Emphasis should be put on training midwives on IPC when providing maternity care. This may help in preventing the spread of infectious diseases including COVID-19 as we observed in the present study.